Clinical case: patient treated for vulvovaginal candidiasis - Tatyana Yu. Pestrikova (Клинический разбор в общей медицине, 2021)
Case study of acute vulvovaginal candidiasis treated with medication containing dequalinium chloride as an active ingredient has been reported. Patient A. aged 26 complaining of vaginal and perineal burning, itching, as well as of profuse white, whitish vaginal discharge, was under observation. Vulvovaginal candidiasis was diagnosed based on the laboratory tests. After verifying the diagnosis the patient was prescribed a medication containing dequalinium chloride, with beneficial effect. No vaginal dysbiosis was reported after exposure to medication.